"Learning Task" Attributable to Students' Stress During the Pandemic Covid-19 - Livana PH; Mohammad Fatkhul Mubin; Yazid Basthomi (Jurnal Ilmu Keperawatan Jiwa, 2020)
The pandemic Covid-19 has turned virtually all learning activities into online. Changing the learning system from face to face to an online system has caused students to be stressed. The present research aims to analyze the factors that cause the students' stress during the pandemic Covid-19. Resorting to both qualitative with phenomenological design and quantitative with descriptive analytic design, this study involved 1,131 students from several provinces in Indonesia. The data were collected from a total sample using a questionnaire in the form of open and closed questions. The data were analyzed using the Colaizzi method and frequency distribution. The analysis shows several themes and the results of its distribution, namely "Learning tasks" (70.29%), "Being bored at home" (57.8%), "Online learning processes that start to get boring" (55.8%), "Inability to meet loved ones "(40.2%), "Inabilityto take part in online learning due to poor connectivity" (37.4%), "Inability to carry out hobbies as usual", (35.8%), "Inability to carry out laboratory practice due to unavailability of tools". The results show that "learning task" was the major factor causing stress to students during the pandemic Covid-19.